Abdominal pain, principles of diagnosis of urgent abdominal surgical pathology - V. I. Podoluzhny (Фундаментальная и клиническая медицина)
Over 80 % of patients seeking treatment at the general surgical hospital on duty complain of abdominal pain. The paper presents current understanding of the dynamics of incidence of common acute abdominal surgical pathology in Kuzbass from 1993 to 2023. A comparative analysis was conducted between the first and last decades and revealed that acute cholecystitis was the leading cause by 2023 − 122 cases per hundred thousand population per year. This level was observed in both the first and third decades. The average annual number of patients treated for acute pancreatitis increased from 64.3 to 109.6 per hundred thousand residents, an increase of 70.4 %. On the contrary, the number of patients with acute appendicitis decreased from 190.8 to 93.5 per hundred thousand, a decrease of 51%. The fourth position is occupied by patients with intestinal obstruction; the incidence in the first and third decades was 41.7 and 45.2 per hundred thousand, respectively, an increase of 8.4%. In the dynamics of thirty-year observation, there was a decrease in the number of people operated on with perforated gastric and duodenal ulcers by 47.3 %, the incidence was 28.8 and 15.2 per 100,000, respectively. On the contrary, the average annual number of people treated with strangulated hernia increased by 35.1 %, the incidence increased from 29.9 to 39.8 per hundred thousand residents of the region. Severe, extremely intense abdominal pain at the onset of the disease is observed in 0.1−2 % of hospitalized patients with acute large-focal pancreatic necrosis, strangulation intestinal obstruction, perforated ulcer, and acute mesenteric ischemia. The lecture outlines the issues of diagnosing urgent abdominal surgical pathology, taking into account the nature, intensity and localization of pain. Issues of surgical tactics for diffuse, non-localized, extremely intense pain and differential diagnosis with peritonism syndrome and pseudoperitonitis are separately considered.